Bidirectional associations between biological aging, cardiovascular health, and cardiovascular risk: findings from the INSPIRE-T lifespan cohort - Mathilde Strumia; Vanina Bongard; Samuel Thuriot; Philippe Cestac; Brigitte Sallerin; Jean-Marc Lemaitre; David Furman; Sophie Guyonnet; Bruno Vellas; Sandrine Andrieu; Laure Rouch; Sophie Guyonnet; et al. (GeroScience, 2026)
Chronological age is a common and non-modifiable factor for chronic disease, but does not fully explain age-related changes. Biological clocks have been developed to explore biological aging mechanisms. They could help identify protective factors against accelerated aging and associated diseases. We aim to assess the association between reduced epigenetic or inflammatory aging and ideal cardiovascular health or cardiovascular risk. We conducted a cross-sectional analysis of participants from the INSPIRE-T cohort. Cardiovascular health (CVH) was assessed using the Life’s Essential 8 score. Cardiovascular risk was assessed using the American Framingham risk score (FRS) and the European Systematic Coronary Risk Evaluation (SCORE2) score. Epigenetic and inflammatory aging was calculated from the residuals from linear regression of biological age (based on five epigenetic clocks and one inflammatory clock) and chronological age. Linear and logistic regression models were used. Better CVH has been associated with slower epigenetic aging, particularly in younger subjects and men. Accelerated epigenetic aging measured by GrimAge was associated with an increase cardiovascular risk (for SCORE2: OR = 1.10 95%CI [1.04; 1.16]). No persistent association was found with the inflammatory clock. Our study reported an association between ideal global CVH with reduced epigenetic aging after adjustment for chronological age and gender. This suggests that epigenetic aging may be modifiable through healthy lifestyle and cardiovascular risk management, although a potential underlying causal relationship remains to be established. Moreover, accelerated epigenetic aging is linked to worsening cardiovascular risk, and could be a new risk factor alongside chronological age. Graphical Abstract

HealthAge: evaluation of intrinsic capacity changes in humans, mice, and killifish to explore the biology of aging - Sophie Guyonnet; Claudie Hooper; Heike A. Bischoff-Ferrari; Angelo Parini; Yohan Santin; Jean-Philippe Pradère; Cédric Dray; Bruno Vellas; Sophie Guyonnet; Bruno Vellas; Lauréane Brigitte; Agathe Milhet; et al. (GeroScience, 2025)
HealthAge was devised by a conglomerate of research groups in Toulouse, France, with the combined goal of narrowing the lifespan-healthspan gap through novel translational bench-to-bedside research studies. HealthAge comprises the “INStitute for Prevention” “healthy aging” and “medicine Rejuvenative” (INSPIRE) human translational, outbred SWISS mice and African turquoise killifish (GRZ strain) cohorts in which aging is studied based on the concept of intrinsic capacity (IC). In this narrative review, we describe the three INSPIRE aging models (human cohort, n = 1109, age range 20 –102 years old with mean age ± standard deviation, 62.4 ± 19.0 years and 61.9% female; outbred SWISS mice, n = 1576 and African Turquoise killifish, n = 300) and explain how IC is assessed at the clinical (in humans) and biological level over time. HealthAge strives to elucidate the underlying biology of IC and to identify biomarkers of IC declines and novel gero-therapeutics using the clinical and biological data and biospecimens collected prospectively in the three species. The data sharing policy will foster scientific discovery through new multi-disciplinary collaborations. Thus, HealthAge will promote healthy aging using a unique translational platform based on IC phenotyping with the ultimate goal of preventing loss of human independence and alleviating health costs associated with an aging population.

The associations between biological markers of aging and appetite loss across adulthood: retrospective case–control data from the INSPIRE-T study - Annelie Turesson; Afsaneh Koochek; Margaretha Nydahl; Jean-Marc Lemaitre; Paul Bensadoun; Laurent O. Martinez; Sophie Guyonnet; Yves Rolland; Bruno Vellas; Philipe De Souto Barreto; Lauréane Brigitte; Agathe Milhet; et al. (GeroScience, 2025)
Appetite loss is a common clinical condition in older adulthood, but how this condition associates with biological aging remains unknown. The present study aims to examine the associations of biological aging markers with appetite loss in community-dwelling people aged 21 to 102 years. This retrospective case–control study used baseline data from the INSPIRE-T cohort in Toulouse, France. Each of the 49 cases with appetite loss was sex- and age-matched to two controls without appetite loss ( n = 147; median age of 79 years, interquartile range: 19.5; 67% women). Appetite loss was assessed using a single yes–no question from the World Health Organization´s Integrated Care for Older People screening tool. Biomarkers (first- and second-generation DNA methylation-based epigenetic clocks [Horvath, Hannum, PhenoAge, and GrimAge], the inflammatory aging clock iAge, and Adenosine triphosphatase inhibitory factor 1—IF1) were derived from blood samples. Logistic regression analyzed the associations of these markers with appetite loss. In fully adjusted models, accelerated aging using GrimAge was the only biomarker associated with appetite loss (Odds Ratio = 1.21, 95% Confidence Interval: 1.03, 1.43). When stratified by age (≤ 65 years vs. > 65 years) and sex, this association remained significant only in individuals over 65 years and men. Future research is needed to explore the potential mechanisms involved, as well as how other biological drivers of aging (e.g., cell senescence, deregulated nutrient sensing) relate to appetite loss.

Association between aging-related biomarkers and longitudinal trajectories of intrinsic capacity in older adults - Wan-Hsuan Lu; Sophie Guyonnet; Laurent O. Martinez; Alexandre Lucas; Angelo Parini; Bruno Vellas; Philipe de Souto Barreto (GeroScience, 2023)

Biomarkers of mitochondrial dysfunction and inflammaging in older adults and blood pressure variability - Leonardo Bencivenga; Mathilde Strumia; Yves Rolland; Laurent Martinez; Philippe Cestac; Sophie Guyonnet; Sandrine Andrieu; Angelo Parini; Alexandre Lucas; Bruno Vellas; Philipe De Souto Barreto; Laure Rouch; et al. (GeroScience, 2023)

Investigating the combination of plasma amyloid-beta and geroscience biomarkers on the incidence of clinically meaningful cognitive decline in older adults - Wan-Hsuan Lu; Kelly Virecoulon Giudici; John E. Morley; Sophie Guyonnet; Angelo Parini; Geetika Aggarwal; Andrew D. Nguyen; Yan Li; Randall J. Bateman; Bruno Vellas; Philipe de Souto Barreto; Bruno Vellas; et al. (GeroScience, 2022)